Acquired demyelinating diseases of the central nervous system in children: A single center experience - Emina Vukas-Salihbegović; Sajra Uzicanin; Zinka Huseinbegovic (Medicinski glasnik, 2025)
Background: Acquired demyelinating diseases (ADD) of central nervous system encompasses a wide spectrum of neurological symptoms depending on the location and the severity of demyelination. The aim of this study is to present the frequency and the clinical, immunological, and radiological characteristics of ADD in pediatric patients at the Pediatric Clinic, Clinical Center University of Sarajevo. Methods: This is a retrospective observational study, conducted between 2017-2024, that included patients under 18 years with ADD. The diagnosis is established through clinical evaluation, characteristic MRI findings, immunological markers, and the exclusion of alternative conditions that mimic ADD, following the IPMSSG (International Pediatric Multiple Sclerosis Study Group ) 2010 criteria. We classified the patients into two groups based on the disease course: monophasic, multiphasic group which is further subdivided into multiple sclerosis (MS) and non-MS multiphasic group. Results: : Forty-one patients with ADD were included in the study. Seventeen patients (17/41, 41.46%) remained monophasic, whereas twenty-four patients (24/41, 58.54%) exhibited a multiphasic course. Within the multiphasic group 22/24 patients (91.67%) were diagnosed with multiple sclerosis (MS), and 2/24 (8.33%) had a non-MS multiphasic disease course. Conclusion: In this study, we presented the frequency and the clinical, immunological, and radiological characteristics of acquired demyelinating diseases in pediatric patients. Recognizing these distinct clinical patterns is crucial for enhancing early diagnostic accuracy and optimizing management strategies in this patient population. Ultimately, our study supports the need for a prospective, multicentric investigation to further consolidate data and refine our understanding of ADD epidemiology in our region.
Keywords: hyperintense lesions; monophasic; multiphasic; multiple sclerosis; non-MS multiphasic